Reward processing deficits: weakened self-reward association in individuals with methamphetamine addiction undergoing abstinence - Yanghui, Xie; Chong, Fan; Qianyu, Li (Frontiers in Psychology, 2025)
This research primarily investigates whether both reward processing and self-processing are aberrant in individuals with methamphetamine use disorder. It also explores whether initiating self-referential processing modulates reward processing abilities in this population, and how this modulation differs from that observed in healthy controls. Experiment 1 employed a two-factor mixed experimental design to compare the performance of addiction groups with varying withdrawal durations (all participants in the addiction groups were methamphetamine users) against healthy control groups in a probabilistic reward learning task. The results indicated that the healthy control group performed better than the addiction group in learning characters associated with high-probability, high-reward outcomes. While the long-term abstinence group outperformed the short-term abstinence group, these differences were not statistically significant. Therefore, the addiction group subjects in Experiments 2 and 3, the addiction group consisted of methamphetamine users with a uniform withdrawal duration of no more than 12 months. Experiment 2 utilized a two-factor mixed design to explore whether self-processing is abnormal in addicted individuals. The results showed that the addiction group had a significantly lower accuracy rate for self-referential characters compared to the healthy control group, while their accuracy for characters associated with acquaintances was significantly higher than that of the healthy control group. Experiment 3 also employed a two-factor mixed design to examine the moderating effect of self-processing on reward learning. The findings revealed that when high-probability reward characters were linked to self-relevance, learning efficiency was superior to that of characters linked to acquaintances. However, this moderating effect was weaker in the addiction group compared to the healthy control group. These results suggest that substance addiction not only impairs individuals' reward processing abilities but also reduces their sensitivity to self-referential information. Furthermore, the enhancing effect of self-processing on reward learning is significantly diminished in addicted populations, providing new insights into the cognitive mechanisms underlying addiction.